MSME Product Bazaar in Gunungmanik Village Efforts to Increase Family Economic Productivity - Arie Susetio utami; johan; Arif Nurudin; Nuri Kartini (Jurnal Abdisci, 2023)
Implementing the Student Work Lecture (KKM) in 2022 is to create a relationshipbetween the academic world and the community through experience through Village Bazaaractivities that benefit students and the community. Village Bazaar activities aim to realizeinnovative ideas to market local MSME products that can be widely promoted. This activity aims to socialize assistance in making MSME products by providing puddingproducts, bofeci (boba coffee ciraja), and broom buns.